2020
DOI: 10.1039/d0sc01559h
|View full text |Cite
|
Sign up to set email alerts
|

Observations of tetrel bonding between sp3-carbon and THF

Abstract: sp3-C⋯THF tetrel bonding was observed in the crystalline state and in the gas phase. Density functional calculations revealed interaction energies up to −11.2 kcal mol−1 and showed that these adducts are held together mainly by electrostatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…TCCP derivatives 1 and 2 are both synthetically accessible in moderate to decent yields (34-58 %) using as traightforward modified literature procedure (see experimental and ESI for full details and characterization). [21] Single crystals suitablef or X-ray diffractionm easurements (see experimental for details) were obtainedb ys low evaporation of as olution of 1 or 2 in dichloromethane. The atomicc oordinates contained within the unit cellsa re shown in Figure 2a and bf or 1 and 2 [23] respectively (see experimental for full details).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TCCP derivatives 1 and 2 are both synthetically accessible in moderate to decent yields (34-58 %) using as traightforward modified literature procedure (see experimental and ESI for full details and characterization). [21] Single crystals suitablef or X-ray diffractionm easurements (see experimental for details) were obtainedb ys low evaporation of as olution of 1 or 2 in dichloromethane. The atomicc oordinates contained within the unit cellsa re shown in Figure 2a and bf or 1 and 2 [23] respectively (see experimental for full details).…”
Section: Resultsmentioning
confidence: 99%
“…[20] We recently reported that the sp 3 -carbon tetrel bondingp otential of dimethyl-TCCP allows for supramolecular adduct formation with the electron-rich O-atom of tetrahydrofuran, both in the solid state and in the gas phase. [21] Here, we exploit and extend on this principle by demonstratingc rystal engineering with sp 3 -C tetrel bonding interactions using TCCP derivatives 1 and 2 ( Figure 1).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This same phenomenon occurs on a divalent chalcogen Y atom, but each of its two RY bonds leads to a separate σ-hole, and a logical extension provides three σ-holes around a Z pnicogen atom in its ZR 3 configuration. Recent works [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] have also included tetrel atoms T (C and Si, etc.) in this category, as the tetravalent TR 4 molecule has four σ-holes, so could, at least in principle, participate in as many as four simultaneous tetrel bonds.…”
Section: Introductionmentioning
confidence: 99%